A Comparative Study of the Life Quality and Style of the Healthy and Asthma Suffering People Referring to Zanjan Province Hospitals - Sassan Rajabi; Mojgan Sadat Aghvamy; Nasrin Bahraminejad; Ramezan Fallah (Zanjan University of Medical Sciences and Health Services, 2020)
Background: Today, asthma is one of the most prevalent chronic respiratory diseases, involving a large number of people and communities. Research show that the disease overshadows the social, psychological and even economic life and performance of the patients. Objectives: This study was conducted in Zanjan Province hospitals with the purpose of comparing the life style and quality of life asthma patients with healthy people. Methods: This study is descriptive-comparative in nature, focusing on two groups of individuals (healthy people and those suffering from asthma) using convenience sampling method to serve the goals of the study. The instruments used for collection of data were the World Health Organization Quality of Life (WHOQOL) questionnaire and the Life Style Questionnaire (LSQ). The data were analyzed using the SPSS software version 16. Results: The demographic data relating to both groups (n=50 for each group) did not show any difference of statistically significant. The mean scores of the life style of the healthy people and the asthma patients were 149.34 and 136.48, respectively (p<0.05). Furthermore, the mean scores of the Quality of Life (QOL) of healthy people and asthmatics were 36.260 and 29.205, respectively (p<0.05). Conclusion: The life style and QOL of asthma patients are deteriorated to a large extent. Therefore, it is recommended that educational interventions to improve the life style and QOL of patients included in their care plan